Phenoxy resin and its molded body

The phenoxy resin with reduced residual solvent and specific molecular weight range addresses the issue of low impact resistance in conventional phenoxy resins, enhancing impact resistance while maintaining other essential properties, thus expanding its application in molded products.

JP7663392B2Active Publication Date: 2025-04-16NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021053429
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-04-16
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Conventional phenoxy resins lack high impact resistance while maintaining flexibility, adhesion, appearance, and handling properties, limiting their application in molded products.

Method used

A phenoxy resin with a residual organic solvent content of less than 0.50 wt%, a weight average molecular weight of 30,000 to 80,000, and specific properties such as boiling point, insoluble material amount, light transmittance, and yellow index, which enhance impact resistance without compromising other properties.

Benefits of technology

The improved phenoxy resin maintains flexibility, adhesion, appearance, and handling properties while significantly enhancing impact resistance, allowing for broader application in molded products and thermoplastic resin compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663392000001
    Figure 0007663392000001
  • Figure 0007663392000002
    Figure 0007663392000002
Patent Text Reader

Abstract

To provide a phenoxy resin that achieves an improvement in impact resistance, which is one of the phenoxy resin's shortcomings, while retaining its flexibility, adhesion, appearance, and handleability.SOLUTION: A phenoxy resin fulfills the following conditions (1) and (2): (1) the amount of residual organic solvent in the resin is less than 0.50 wt.%; and (2) the weight average molecular weight is 30000-80000.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a phenoxy resin having excellent impact resistance and a molded article thereof, as well as a thermoplastic resin composition containing a phenoxy resin and a molded article thereof. [Background technology]

[0002] Thermoplastic polyhydroxy polyether resins, known as phenoxy resins, are used in a wide range of applications in the electronics field, such as insulating films and adhesive films, due to their excellent flexibility, adhesion, etc. They have also been used as a modifying resin for the matrix resin of fiber-reinforced composite materials to improve mechanical properties, thermal properties, and adhesion to carbon fibers.

[0003] In recent years, the range of applications of phenoxy resin has expanded, for example by forming it into fibers and using it to fix unidirectional reinforcing fiber substrates or as the matrix resin itself in fiber-reinforced composite materials. However, although it has excellent performance, it has the drawback of not having high impact resistance when molded into a molded product.

[0004] Patent Documents 1 and 2 disclose that in a method for producing a thermoplastic resin composition containing an amorphous thermoplastic resin, the residual solvent in the entire composition is removed to reduce the content to less than 1 wt%, thereby preventing gelation and carbonization and improving the moldability of the composition and the impact resistance of a molded product. However, no consideration is given to the residual solvent in the thermoplastic resin itself, and the documents merely disclose that an organic solvent is added externally when at least two types of thermoplastic resins are melt-kneaded, and the content of the added organic solvent is reduced to less than 1 wt% in the final composition. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 7-26024 [Patent Document 2] Japanese Patent Application Publication No. 5-310951 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention aims to provide a phenoxy resin which has improved impact resistance while maintaining the flexibility, adhesion, appearance and handleability of the phenoxy resin. [Means for solving the problem]

[0007] As a result of extensive research, the present inventors have discovered a phenoxy resin that has significantly improved impact resistance, which has been a problem with conventional phenoxy resins. That is, the present invention relates to a phenoxy resin that satisfies the following conditions (1) and (2). (1) The residual amount of organic solvent in the resin is less than 0.50 wt% (2) Weight average molecular weight is 30,000 to 80,000

[0008] In addition, the phenoxy resin of the present invention is one in which the boiling point of the residual organic solvent exceeds 100°C and the amount of insoluble matter is 30 ppm or less, and it is desirable that the total light transmittance is 85% or more and the yellow index is less than 6.

[0009] The present invention further includes a molded article of the phenoxy resin, or a resin composition containing the phenoxy resin, and a molded article thereof. Effect of the Invention

[0010] The phenoxy resin of the present invention maintains the flexibility, adhesion, appearance, and handleability of phenoxy resin while improving the impact resistance, which was a problem, and this will greatly expand the use of phenoxy resin in molded articles, which has previously been difficult to apply. Furthermore, by using the phenoxy resin of the present invention as a toughness improver in combination with a thermoplastic resin such as a polyamide resin, the impact resistance of the thermoplastic resin composition can be improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The phenoxy resin of the present invention is characterized in that the amount of residual volatile matter such as water and organic solvent, particularly the amount of residual organic solvent (solvent), is controlled to a certain value or less. It is essential that the amount of residual organic solvent in the phenoxy resin is less than 0.5 wt%. If the amount of residual organic solvent exceeds 0.5 wt%, the impact resistance will remain at roughly the same level as conventional phenoxy resins that contain about 1 wt% residual solvent, and at this level, reducing the residual solvent will not have any effect on improving impact resistance. It is presumed that the residual solvent vaporizes due to the heat during molding and becomes microvoids, which become the starting point of destruction when an impact is applied, but by reducing the amount of residual solvent to less than 0.5 wt%, not only does the frequency of void occurrence decrease, but the amount of solvent incorporated into the structure is reduced, allowing the resin itself to withstand foaming, which is presumed to suppress the occurrence of voids themselves. The residual solvent content is preferably 0.45 wt% or less, more preferably 0.40 wt% or less. Although there is no particular lower limit, reducing the residual solvent content to less than 0.03 wt% requires a longer devolatilization treatment time, which may result in a decrease in appearance due to an increase in the yellow index value (YI value) or a decrease in light transmittance, or a decrease in mechanical properties due to thermal degradation of the resin.

[0012] Regarding residual organic solvents, it is preferable to control the residual amount to the above-mentioned upper limit or less for those with a boiling point exceeding 100° C. It is also preferable that the concentration of organic solvents having a boiling point of less than 100° C. in the phenoxy resin is as low as possible, but compared with high-boiling point solvents, they are more likely to be eliminated together with moisture during drying treatment.

[0013] As for moisture, which is a volatile component other than organic solvents, there is no particular problem as long as it is within the range specified by general management methods for resin materials used in molding, but it is preferably 0.1 wt% or less.

[0014] The phenoxy resin of the present invention preferably has a yellow index (YI) value of less than 6 and a total light transmittance of 85% or more. Coloration or reduced transparency of the resin, such as a YI value of more than 6 or a total light transmittance of 85% or less, not only reduces the appearance, which is a characteristic of phenoxy resin, but also may reduce the mechanical properties of the resin due to excessive devolatilization treatment conditions.

[0015] The amount of insoluble matter in the phenoxy resin is preferably 30 ppm or less. Insoluble matter is a three-dimensional crosslinking reaction product that occurs locally for some reason, and is confirmed in the solution as a gel-like foreign matter when the phenoxy resin is dissolved in an organic solvent such as methyl ethyl ketone (MEK). Insoluble matter not only deteriorates the appearance of the molded body as a foreign matter, but also becomes the starting point of destruction when the molded body is subjected to an external impact. For this reason, it is preferable that the amount of insoluble matter is as small as possible, and more preferably 25 ppm or less.

[0016] The mass average molecular weight (Mw) of the phenoxy resin is desirably in the range of 30,000 to 80,000. It is preferably 30,000 to 70,000, and more preferably 30,000 to 60,000. When the Mw of the phenoxy resin is within the above range, the strength of the molded article can be sufficiently ensured, and the same processability and moldability as those of conventional phenoxy resins can be maintained. The Mw is a value measured by gel permeation chromatography and converted using a standard polystyrene calibration curve.

[0017] Next, a method for obtaining the phenoxy resin of the present invention will be described.

[0018] The phenoxy resin of the present invention can be obtained by a condensation reaction between a dihydric phenol compound and an epihalohydrin, or a polyaddition reaction between a dihydric phenol compound and a difunctional epoxy resin, and can be obtained by a conventionally known method in solution or in the presence of a small amount of an organic solvent, or without a solvent.

[0019] Examples of dihydric phenol compounds used in the production of phenoxy resins include hydroquinone, resorcinol, 4,4-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ketone, 2,2-bis(4-hydroxyphenyl)propane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 2,2-bis(4-hydroxyphenyl)butane, and 1,1-bis(4-hydroxyphenyl)-1-phenylethane. , bis(4-hydroxyphenyl)diphenylmethane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, 2,2-bis(3-phenyl-4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3-tert-butylphenyl)propane, 1,3-bis(2-(4-hydroxyphenyl)propyl)benzene, 1,4-bis(2-(4-hydroxyphenyl)propyl)benzene, 2,2-bis(4-hydroxyphenyl)-1,1,1-3,3,3-hexafluoropropane, 9,9'-bis(4-hydroxyphenyl)fluorene, etc. Among these, 4,4-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ketone, 2,2-bis(4-hydroxyphenyl)propane, or 9,9'-bis(4-hydroxyphenyl)fluorene is particularly preferred in terms of physical properties and cost.

[0020] Examples of bifunctional epoxy resins used in the production of the phenoxy resin include epoxy oligomers obtained by condensation reaction of the above-mentioned dihydric phenol compounds with epihalohydrin, such as hydroquinone diglycidyl ether, resorcinol diglycidyl ether, bisphenol S type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, methylhydroquinone diglycidyl ether, chlorohydroquinone diglycidyl ether, 4,4'-dihydroxydiphenyloxide diglycidyl ether, 2,6-dihydroxynaphthalene diglycidyl ether, dichlorobisphenol A diglycidyl ether, tetrabromobisphenol A type epoxy resin, and 9,9'-bis(4)-hydroxyphenyl)fluorene diglycidyl ether. Among these, in terms of physical properties and cost, bisphenol A type epoxy resin, bisphenol S type epoxy resin, hydroquinone diglycidyl ether, bisphenol F type epoxy resin, tetrabromobisphenol A type epoxy resin, and 9,9'-bis(4)-hydroxyphenyl)fluorene diglycidyl ether are particularly preferred.

[0021] The reaction solvent used in the production of phenoxy resin in the presence of a reaction solvent (solvent) is not particularly limited as long as it does not inhibit the reaction, and examples of the reaction solvent include aromatic hydrocarbons such as benzene (bp 80°C), toluene (bp 111°C), and xylene (bp 139°C), and alcohols such as methanol (bp 65°C), ethanol (bp 78°C), propanol (bp 97°C), n-butyl alcohol (bp 118°C), and isopropyl alcohol (bp 83°C). ketones such as acetone (bp 56°C), methyl ethyl ketone (bp 80°C), methyl isobutyl ketone (bp 116°C), 2-heptanone (bp 151°C), 2-octanone (bp 173°C), cyclopentanone (bp 131°C), cyclohexanone (bp 155°C), acetylacetone (bp 140°C), etc.; esters such as methyl acetate (bp 57°C), ethyl acetate (bp 77°C), butyl acetate (bp 126°C), butyrolactone (bp 204°C), etc.; Examples of organic solvents include ethers such as diethyl ether (bp 35° C.), dibutyl ether (bp 141° C.), t-butyl methyl ether (bp 55° C.), dioxane (bp 101° C.), tetrahydrofuran (bp 66° C.), and acetophenone (bp 202° C.); glycol ethers such as ethylene glycol monomethyl ether (bp 124° C.), ethylene glycol monoethyl ether (bp 135° C.), and diethylene glycol monomethyl ether (bp 194° C.); amides such as N-methylformamide (bp 182° C.), N,N-dimethylformamide (bp 153° C.), N,N-dimethylacetamide (bp 165° C.), 2-pyrrolidone (bp 245° C.), and N-methylpyrrolidone (bp 204° C.); sulfoxides such as dimethyl sulfoxide (bp 189° C.); and sulfones such as sulfolane (bp 287° C.). These may be combined in combination or may be mixed with an organic solvent and an inorganic solvent (such as water). The phenoxy resin obtained by the solvent reaction may be directly transferred to the devolatilization step, but it is preferable to carry out a solvent removal treatment in advance to form solid resin pellets in which the residual solvent has been reduced to about several wt %.

[0022] As reaction catalysts that can be used in the production of the phenoxy resin, conventionally known polymerization catalysts such as alkali metal hydroxides, tertiary amine compounds, quaternary ammonium compounds, tertiary phosphine compounds, quaternary phosphonium compounds, and imidazole compounds are preferably used.

[0023] In obtaining the phenoxy resin of the present invention, the mass average molecular weight (Mw) of the phenoxy resin (a) is usually 10,000 to 200,000, preferably 20,000 to 100,000, and more preferably 30,000 to 80,000. If Mw is too low, the strength of the molded article tends to be poor, and if Mw is too high, the workability and processability tend to be poor.

[0024] The hydroxyl equivalent (g / eq) of the phenoxy resin is usually 50 to 1000, preferably 100 to 750, and particularly preferably 200 to 500. If the hydroxyl equivalent is too low, the water absorption rate increases due to an increase in the number of hydroxyl groups, whereas if the hydroxyl equivalent is too high, the adhesiveness, which is a characteristic of the phenoxy resin, tends to decrease, which is undesirable.

[0025] The produced phenoxy resin is then subjected to a volatilization operation, but depending on the production method of the phenoxy resin, it is desirable to remove excess solvent using a thin-film evaporator or the like and pelletize it. At this time, if the organic solvent content in the pellets is adjusted to about 1 to 5 wt%, it is advantageous because the time required for the next volatilization operation can be shortened.

[0026] The devolatilization operation is not particularly limited as long as it can reduce the amount of residual organic solvent in the phenoxy resin to less than 0.5 wt% and does not cause deterioration in the YI value or total light transmittance, and a devolatilization assistant may also be used. In addition, the apparatus used for devolatilization can be a devolatilization extruder, a high-viscosity thin-film evaporator, or the like, without any particular limitation. The resin after the degassing operation is pelletized and processed into a molded product in a subsequent step (molding step), but the degassing operation and the molding step may be carried out consecutively.

[0027] The phenoxy resin of the present invention can be injection- or extrusion-molded, and can be made into a molded product, film, or fiber having a complex shape. It can also be used as a fiber-reinforcing material by impregnating a reinforcing fiber substrate such as glass fiber or carbon fiber as a matrix resin. In this case, if necessary, conventionally known additives such as flame retardants, impact resistance improvers, antistatic agents, slip agents, antiblocking agents, lubricants, anti-fogging agents, organic fillers, and inorganic fillers may be appropriately selected and used.

[0028] The phenoxy resin of the present invention can also be used as a matrix resin for various molded articles or fiber-reinforced plastics as a thermoplastic resin composition imparted with toughness by blending it with a thermoplastic resin such as polyamide or aromatic polyester. When blending with a thermoplastic resin such as polyamide or aromatic polyester, it is preferable to melt-knead the pellets using a twin-screw extruder, etc. There is no particular restriction on the blending ratio, but if the characteristics of the phenoxy resin are to be expressed in the resin composition, it is preferable to use 20 to 80 parts by weight of the phenoxy resin per 100 parts by weight of the resin composition.

[0029] The phenoxy resin of the present invention can be processed into various forms such as molded articles by pressing, extrusion, or injection molding, fibers, films, powders, etc., and has the characteristics of phenoxy resin, such as flexibility, adhesion, and appearance, and is also significantly improved in impact resistance compared to conventional phenoxy resins. For example, the Charpy impact strength is 10.0 kJ / m 2 Therefore, it can be used in a wide range of fields, from consumer electrical and electronic equipment to industrial equipment, automobiles, and aircraft. EXAMPLES

[0030] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the description of these examples. The methods for testing and measuring various physical properties in the examples and comparative examples are as follows.

[0031] [Organic solvent-based residual volatile matter] The sample was heated in an electric furnace (He gas atmosphere) at 200°C for 15 minutes, and the evaporated residual solvent was collected in a TENAX collection tube. The collected material was then measured by GC-MS (5975 inert GC / MS system, Agilent Technologies, column: HP-5ms, column temperature: 40°C (2min HOLD) → 180°C (10°C / min), carrier gas: He (1mL / min), ionization method: EI (70eV)) to analyze the organic solvent content. The organic solvents detected were toluene and n-butyl alcohol, and the combined amounts of these are listed in Table 1 as the organic solvent volatiles.

[0032] [Amount of insoluble matter] 100 g of sample was weighed out to the nearest 0.01 g and placed in a flask, and cyclohexanone was added as a dissolving solvent, and the mixture was dissolved at room temperature or by heating. Visually confirm that there was no dissolved residue, and use this as the sample solution. A washed and dried 325 mesh wire mesh was weighed out. The sample solution was filtered through the wire mesh, and the sample solution remaining in the flask was also washed with cyclohexanone, and this washing liquid was also filtered through the wire mesh. This wire mesh was placed in a constant temperature dryer at 50°C and dried. The wire mesh was cooled to room temperature, and the amount of insoluble matter was calculated using the formula below.

number

[0033] [Average molecular weight] Analysis was performed using a Tosoh Corporation HLC-8320GPC. The columns were a TSKguardcolumnHXL, a TSKgel GMHXL, a TSKgel GMHXL, and a TSKgel G2000HXL connected in series, and the column oven was set to 40°C. The eluent was tetrahydrofuran, and the detector was an RI detector. The flow rates were 1 mL / min on the sample side and 0.5 mL / min on the reference side. Approximately 0.1 g of the laminate was weighed out, dissolved in 10 mL of tetrahydrofuran containing 5% cyclohexanone as an external standard substance, and filtered through a 0.45 μm PTFE membrane filter for analysis. The molecular weight was converted using a standard polystyrene calibration curve, and the elution time was corrected using cyclohexanone.

[0034] [Tensile properties] In accordance with JIS K 7161:2014 Plastics - Test method for tensile properties, the tensile properties of test pieces made of matrix resin (thermoplastic resin composition) produced using an injection molding machine were evaluated.

[0035] [Bending properties] In accordance with JIS K 7171:2016 Plastics - Test method for bending properties, the bending properties of test pieces made of matrix resin (thermoplastic resin composition) produced using an injection molding machine were evaluated.

[0036] [Charpy impact strength] A Charpy impact tester (Yasuda Seiki Seisakusho Co., Ltd., No. 258PC-S) was used. The Charpy impact test was performed at room temperature on a multipurpose test piece with a length of 80 mm, width of 10 mm, and thickness of 4 mm, with a V-notch 2 mm deep penetrating the plate thickness, with the longitudinal direction of the test piece in the MD direction. The absorbed energy was calculated from the difference in hammer potential energy before and after the fracture of the test piece, and this was taken as the Charpy impact strength.

[0037] [Deflection temperature under load] A deflection temperature under load tester (Yasuda Seiki Seisakusho Co., Ltd., No. 148-HDPC-3) was used. A multipurpose test piece with a length of 80 mm, width of 10 mm, and thickness of 4 mm was subjected to a bending stress of 0.45 MPa at a span of 64 mm while the temperature of the oil bath was raised at a rate of 120°C / min., and the temperature at which the specified deflection (0.34 mm) was reached was recorded as the deflection temperature under load.

[0038] [Melt flow rate (MFR)] Measurements were performed in accordance with JIS K 7210 (temperature: 230°C, load: 2.16 kg).

[0039] [Total light transmittance] A 3 mm flat test piece was prepared, and the total light transmittance was measured using a haze meter (NDH7000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0040] [Yellow Index (YI value)] A 3 mm thick plate test piece was prepared, and the YI value (yellow index indicating the degree of yellowing) was measured using a color difference meter (NDJ400, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0041] In obtaining the phenoxy resin of the present invention, a commercially available phenoxy resin was used. [Phenoxy resin] Phenototo YP-50S (bisphenol A type, Mw=40,000, non-volatile content 98.5wt%, moisture 0.35wt%), manufactured by Nippon Steel Chemical & Material Co., Ltd.

[0042] Example 1 A multi-stage vented twin-screw extruder (Plastic Engineering Research Institute Co., Ltd., screw diameter = 30 mm, L / D = 40) was used to carry out the devolatilization process of phenoxy resin YP-50S. The extruder was set at a temperature of 280°C, a screw speed of 200 rpm, a feed rate of 20 kg / hr, and a vent pressure of 5 mmHg. The phenoxy resin after devolatilization was extruded from a strand die, cut with a strand cutter and pelletized again, after which test pieces were prepared for evaluation and various evaluations were carried out. The evaluation results are shown in Table 1.

[0043] Example 2 Devolatilized phenoxy resin pellets were prepared in the same manner as in Example 1, except that the screw rotation speed was changed to 240 rpm and the feed rate was changed to 40 kg / hr. Then, test pieces for evaluation tests were prepared and various evaluations were performed. The evaluation results are shown in Table 1.

[0044] Example 3 The devolatilization process of phenoxy resin YP-50S was carried out using a single-stage vented single screw extruder (Ishinaka Iron Works Co., Ltd., screw diameter = 57 mm, L / D = 40). The extruder was set at a temperature of 280°C, a screw speed of 300 rpm, a feed rate of 150 kg / hr, and a vent pressure of 75 mmHg. The phenoxy resin after devolatilization was extruded from a strand die, cut with a strand cutter and pelletized again, after which test pieces were prepared for evaluation and various evaluations were carried out. The evaluation results are shown in Table 1.

[0045] Comparative Example 1 Test pieces were prepared using pellets of phenoxy resin YP-50S that had not been subjected to devolatilization treatment, and various evaluations were carried out. The evaluation results are shown in Table 1.

[0046] [Table 1]

[0047] By degassing the phenoxy resin and reducing the organic solvent volatile content to 0.5 wt% or less, the Charpy impact strength of the phenoxy resin after degassing is 10 kJ / m 2 The Charpy impact strength was improved significantly by further advancing the devolatilization, and in Example 1, in which the organic solvent-based volatile content was reduced to 0.04 wt%, the value was nearly twice that of Comparative Example 1 before treatment. On the other hand, no yellowing of the phenoxy resin, no decrease in total light transmittance, mechanical properties, etc. was observed, and there was almost no change in the molecular weight, melt flow rate, etc., so it is clear that the phenoxy resin of the present invention maintains the same handleability as conventional phenoxy resins.

Claims

1. A phenoxy resin characterized by satisfying the following conditions (1) and (2): (1) The amount of organic solvent remaining in the resin is less than 0.50 wt%. (2) Weight average molecular weight of 30,000 to 80,000

2. 2. The phenoxy resin according to claim 1, wherein the boiling point of the residual organic solvent is above 100°C.

3. 3. The phenoxy resin according to claim 1, wherein the amount of insoluble matter is 30 ppm or less.

4. The phenoxy resin according to any one of claims 1 to 3, which has a total light transmittance of 85% or more and a yellow index of less than 6.

5. A molded article of the phenoxy resin according to any one of claims 1 to 4.

6. A thermoplastic resin composition comprising the phenoxy resin according to any one of claims 1 to 4.

7. A molded article of the thermoplastic resin composition according to claim 6.

Citation Information

Patent Citations

  • Production of PPE-containing thermoplastic molding composition

    JP1987185744A

  • Method for producing thermoplastic resin compositions

    JP1993310951A

  • Production of amorphous thermoplastic resin composition

    JP1995026024A

  • Phenoxy resin composition and cured article thereof

    JP2018204035A